2016
DOI: 10.1149/2.0031607jes
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Performance Degradation of (La,Sr)(Co,Fe)O3-δSolid Oxide Fuel Cell Cathodes

Abstract: Symmetric cells with porous La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) electrodes on Gd 0.1 Ce 0.9 O 1.95 (GDC) electrolytes were aged at 800 • C for 800 hours in ambient air. Electrochemical impedance spectroscopy (EIS) measurements performed periodically at 700 • C showed a continuous increase of the polarization resistance from 0.15 to 0.34 · cm 2 . Three-dimensional (3D) tomographic analysis using focused ion beam-scanning electron microscopy (FIB-SEM) showed negligible changes due to the ageing, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
99
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 38 publications
28
99
3
Order By: Relevance
“…The bulk device properties of batteries, solid‐oxide fuel cells (SOFC), and other electrochemically active devices depend heavily on the intrinsic properties of the constituent materials and on the overall device microstructure. This understanding has long guided the development of SOFC's, where oxidation/reduction efficiencies and ionic/electronic transport properties were connected to tortuosity and triple‐phase boundary lengths 1–10. In recent years, battery research groups developed a similar focus as multiple studies connected performance degradation to changes in electrode microstructure, including particle fracture, transition metal distribution, surface reconstruction, and elemental dissolution 11–14.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk device properties of batteries, solid‐oxide fuel cells (SOFC), and other electrochemically active devices depend heavily on the intrinsic properties of the constituent materials and on the overall device microstructure. This understanding has long guided the development of SOFC's, where oxidation/reduction efficiencies and ionic/electronic transport properties were connected to tortuosity and triple‐phase boundary lengths 1–10. In recent years, battery research groups developed a similar focus as multiple studies connected performance degradation to changes in electrode microstructure, including particle fracture, transition metal distribution, surface reconstruction, and elemental dissolution 11–14.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cobalt-and ferritebased perovskites have the drawback of forming insulating phases with pyrochlore-type materials, such as La2Zr2O7 (LZO) and Pr2Zr2O7 (PZO), and with perovskite structure such as SrZrO3 (SZO), at the interface between the electrode and the YSZ electrolyte [16]. Such materials have very poor oxygen ionic conductivity even at high temperature, which results in a high additional ohmic resistance [17]. To prevent the zirconate formation, Gd-doped ceria (GDC) has been considered as an alternative electrolyte for low temperature SOFCs, and is also one of the most efficient interlayers set between the cathode and YSZ electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these experimental and theoretical studies it is clear that the mechanism of the oxygen reduction reaction on cobaltite-based cathodes is strongly dependent on the surface morphology of the co-existing A-site and B-site metal atoms. Numerous experimental studies have shown that bulk LSCF cathodes prepared by using conventional ceramic technologies are terminated by a SrO layer 22 with inhomogeneous surface segregation under aging and formation of thicker islands. 32 The formation of other secondary phases such as Sr(OH) 2 and SrCO 3 as reaction products during aging was also commonly observed.…”
mentioning
confidence: 99%